Perancangan User Experience Aplikasi Lapor Vaksin Kelurahan Menggunakan Metode UCD (User Centered Design) - Putra, Gifari Yudiya; Andrianingsih, Andrianingsih; Aldisa, Rima Tamara (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Urban village is an administrative division of the area under the auspices of the sub-district formed by the sub-district government to assist the implementation of the government in development and society. With the current Covid situation, the kelurahan has an important role to help the government accelerate to implement the program evenly. The problem faced by the community is the lack of information on where and when there is a vaccination schedule. Therefore, in order applications that provide information about vaccines. Based on this problem, the authors conducted testing on 302 respondents using the User Centered Design method and the application of the usability method by prioritizing three aspects with the results, namely learmability, efficiency, and staisfacation. User success rate is 91.10%, time-based efficiency is 0.061794869 and system usability scale is 61.42. the existence of this vaccine report application was built to make it easier for sub-districts to record who has not implemented the vaccine and provide notifications about the nearest mass vaccination program